(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Each of the study of related literature implies locating,reading and evaluating report of research as well as reports of casualobservation and opinion that are related to individually planned research. Itwill render valuable clues to the investigator. In the words of Good "thekey to the vast store house of published literatw’e may open door to sources ofsignificant problems and explanatory hypothesis, and provide helpful orientationfor definition of the problem, background of selection procedure andcomparative data interpretation of results. In order to be truly creative andoriginal one must read extensively and critically as a stimulus to thinking.